LO031: The epidemiology of emergency department visits for dog-related injuries in Alberta. (2nd June 2016) - Jelinski, S.E.; Phillips, C.; Doehler, M.; Rock, M.; Checkley, S.; Rowe, B.H.
Abstract : Introduction: Injuries due to interactions with dogs (e.g. bites, collisions, etc) are an important public health concern from both a health and an economic perspective. The consequences of these injuries can be both physical (injury, pain, infection, disfiguration) and psychological. The purpose of this study is to understand the prevalence and characteristics of dog-related injuries among patients presenting to Alberta emergency departments (EDs). Further, this study describes the burden of these injuries on ED economic health care resources.Methods: This retrospective, administrative database cohort study utilised the National Ambulatory Care Reporting System (NACRS) to identify all visits made to Alberta EDs in fiscal years 2010/11 through 2014/15 for dog-related injuries. ED visits where the International Statistical Classification of Diseases and Related Health Problems, 10 th Revision, Canada (ICD-10-CA) code "W54-Bitten or Struck by Dog" appeared in the first four diagnosis fields were captured. The Canadian Institute for Health Information costing model utilising the Comprehensive Ambulatory Classification System and Resource Intensity Weights was employed to calculate average unit health care costs for ED visits excluding physician fees. Data were analyzed using descriptive statistics.Results: During the 5 year study period, Albertans made 21, 821 ED visits for dog-related injuries. The ED visit rate was highest in children under 2 years of age, namely 234 per 100, 000 for males and 206 per 100, 000 for females. ED visit rates were highest for patients residing in the northern health region of the province (220/100, 000) compared to metropolitan areas (90/100, 000 and 64/100, 000 for Edmonton and Calgary zones respectively). One third of visits occurred in the summer months, with a greater proportion of visits occurring on the weekend (34.4%). The predominant areas of injury were wrist/hand/fingers (n=7756 visits; 35.5%) and head/face/neck (n=5152 visits; 23.6%). In 287 visits (1.3%), the patient was admitted to hospital. ED visit costs were highest for children 4 years of age and younger ($243.86/visit; p<0.001).Conclusion: Dog-related injuries result in a substantial number of ED visits and significant costs in Alberta. Understanding the characteristics of these injuries provides an opportunity for prevention, including strategies focussed on higher risk groups involving children and residents of rural areas.